Research progress on the mechanism of non-alcoholic fatty liver disease caused by hepatic insulin resistance - ZHANG Ruonan, HE Junhua (Zhongguo linchuang yanjiu, 2024)
Non-alcoholic fatty liver disease (NAFLD) refers to a clinicopathological syndrome characterized by macrovesicular steatosis and lipid accumulation of hepatocytes, except for alcohol and other specific factors associated with liver damage. In terms of etiology, NAFLD is highly correlated with hepatic insulin resistance (IR). Elucidation of the pathogenesis of hepatic IR is expected to provide theoretical support for drug research in NAFLD. Therefore, this article reviews the research progress on the mechanism of NAFLD caused by hepatic IR.